The performance of massive MIMO systems under correlated channel - Xin Fang; Sheng Fang; Na Ying; Haiyan Cao; Chao Liu (Proceedings - IEEE International Conference on Networks, 2013)
Most researches on the massive multiple-input multiple-output (MIMO) systems are based on the assumption that the MIMO channels are independent, in reality, the above assumption is very difficult to realize when the number of multiple antennas are very large. Hence the simulation on massive MIMO systems under correlated channels has some degree of guiding significance for practical application of massive MIMO systems. Simulation results show that the performance of massive MIMO systems becomes worse when the correlation coefficients of the channels increase. And when the channel correlation coefficient becomes smaller than a certain small value, the performance of massive MIMO systems will be enhanced quickly as the number of Base Station (BS) antennas increases; while the channel correlation coefficient is larger than the certain value, the performance is enhanced slowly as the number of BS antennas increases.